The Impact of Artificial Intelligence on Healthcare: A Systematic Review of Innovations, Challenges, and Ethical Considerations - Hewa Majeed Zangana; Zina Bibo Sallow; Banaz Abed Salih (PT. Delitekno Media Madiri, 2025)
Artificial Intelligence (AI) is revolutionizing healthcare by providing innovative solutions for diagnosis, treatment, and patient care. This systematic review examines recent advancements in AI-driven technologies, focusing on their applications in clinical decision support, operational optimization, and precision medicine. Findings highlight significant improvements in diagnostic accuracy, personalized treatment plans, and healthcare delivery efficiency. Despite these advancements, the integration of AI poses challenges, including concerns about data privacy, algorithmic bias, and the transparency of AI systems. Ethical considerations, such as ensuring equity, protecting patient rights, and maintaining trust in AI-driven interventions, are also critically assessed. The review underscores the importance of responsible innovation, proposing strategies for ethical deployment and regulatory oversight to mitigate potential risks. This comprehensive overview provides valuable insights into the transformative potential of AI in healthcare, alongside its associated challenges and ethical imperatives.